2022
DOI: 10.21203/rs.3.rs-2373370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of the Mechanisms of Drying During CO2 injection into Saline Reservoirs

Abstract: A viable CO2 storage resource must have sufficient storage capacity, reliable containment efficiency and adequate well injectivity. Deep saline formations stand out in terms of storage capacity and containment efficiency. However, formation brine dry-out and salt precipitation in the near well region could impair CO2 injectivity in deep saline reservoirs, thus reducing their potential for CO2 storage. Core-flood experiments and analytical modelling were used to investigate various mechanisms of external and in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…Evaporation of porous media has garnered significant attention as a result of its wide applicability to engineering processes. Both the precipitation of salts and the detachment and capture of small particles have been observed experimentally for sandstone cores (Sokama‐Neuyam et al., 2023). Results have shown that not only do both of these processes result in a decrease in permeability (leading to lower injectivity for CO 2 storage wells), but that these processes can influence each other over the course of injection due to their combined effect on the pore space geometry (Yusof et al., 2022).…”
Section: Introductionmentioning
confidence: 88%
“…Evaporation of porous media has garnered significant attention as a result of its wide applicability to engineering processes. Both the precipitation of salts and the detachment and capture of small particles have been observed experimentally for sandstone cores (Sokama‐Neuyam et al., 2023). Results have shown that not only do both of these processes result in a decrease in permeability (leading to lower injectivity for CO 2 storage wells), but that these processes can influence each other over the course of injection due to their combined effect on the pore space geometry (Yusof et al., 2022).…”
Section: Introductionmentioning
confidence: 88%